Dampak Kekerasan Dalam Rumah Tangga (KDRT) Bagi Kejiwaan Anak Laki Laki Dan Perempuan Di Fakultas Hukum Universitas Tjut Nyak Dhien Medan - Dahris Siregar; Karolina sitepu; Elyani Elyani (Journal Of Human And Education (JAHE), 2023)
This service activity examines the psychological effects of domestic abuse on children. Her background includes the increasing incidence of domestic violence and the importance of understanding its impact on children's psychiatry. This study's aim was to pinpoint the psychological and emotional impact of Psychiatric effects of domestic abuse on children. The method of implementing the activities used was through seminars and discussions held at the faculty of law, Tjut Nyak Dhien University, Medan, which were attended by law faculty students and lecturers as resource persons. The results of this service activity show that domestic violence can cause emotional trauma, mental health disorders, decreased self-esteem, behavior disorders, learning problems, and difficulties in social relationships in children. In conclusion, appropriate protection and attention should be given to children affected by domestic violence to support their recovery and mental well-being.